2014
DOI: 10.1002/yd.20106
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based fitness promotion in an afterschool setting: Implementation fidelity and its policy implications

Abstract: Little is known about how the adoption of evidence-based physical activity (PA) curricula by out-of-school time (OST) programs affects children's physical fitness, and there are no clear guidelines of what constitutes reasonable gains given the types of PA instruction currently offered in these programs. Using a three-wave, quasi-experimental, naturalistic observation design, this study evaluated the implementation of an evidence-based PA instruction curriculum (Sports, Play, and Active Recreation for Kids [SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Previous research has suggested that higher MVPA in OSHC programs is associated with availability of physical activity equipment, as well as the staff not being involved in other behaviours or off task [29]. It has also been suggested that providing children with free-play opportunities can favourably impact MVPA behaviour in out of school care [29, 30]. Whilst this study did not confirm these findings, some of our observations were broadly consistent with this.…”
Section: Discussionsupporting
confidence: 63%
“…Previous research has suggested that higher MVPA in OSHC programs is associated with availability of physical activity equipment, as well as the staff not being involved in other behaviours or off task [29]. It has also been suggested that providing children with free-play opportunities can favourably impact MVPA behaviour in out of school care [29, 30]. Whilst this study did not confirm these findings, some of our observations were broadly consistent with this.…”
Section: Discussionsupporting
confidence: 63%